A case of hypoparathyroidism with cardiovascular complications: interventricular septal dissecting aneurysm in a middle-aged woman - Ronghua Huang; Yi Zhou; Xingshou Pan; Liufang Zhou; Zhengjiang Liu (BMC Endocrine Disorders)
Abstract Background Hypoparathyroidism (HypoPT) is a rare endocrine disease characterized by hypocalcemia, hyperphosphatemia, and insufficient or no parathyroid hormone (PTH) secretion. Hypoparathyroidism-induced chronic hypocalcemia may lead to cardiovascular complications, including myocardial dysfunction and arrhythmias. Interventricular septal dissecting aneurysm, a rare cardiac anomaly, typically arises following structural or ischemic heart disease. This disease can lead to ventricular septal rupture and aneurysmal cystic chamber formation, causing changes in cardiac structure and hemodynamics as well as giving rise to various heart complications. Case presentation No study has reported an association between hypocalcemia and cardiac masses. We encountered a case of hypoparathyroidism in a middle-aged woman who developed an interventricular septal dissecting aneurysm. Upon examination, we found that HypoPT has a profound impact on the heart. Conclusions Hypocalcemia caused by HypoPT can result in structural changes in the heart and myocardial injury. Furthermore, there is a potential link between HypoPT and cardiac aneurysm. The development of an interventricular septal dissecting aneurysm can lead to various cardiac complications; therefore, its early diagnosis and treatment are necessary.